Tanggapan Peserta Didik Kelas XII Jurusan Teknik Komputer dan Jaringan terhadap Penggunaan Google Classroom sebagai Upaya Peningkatan Kemandirian Belajar - Arie Sumartini; Indri Astuti; Afandi Afandi (Journal on Education, 2022)
Since revolution 4.0 and the outbreak of COVID 19, the world of education has been required to be able to transform from a face-to-face learning system to a distance learning system. Teachers have the flexibility of time to share scientific studies and provide independent assignments to students. In addition, teachers can also open discussion rooms for students online (Putri & Dewi, 2019). Independent learning is the readiness of individuals who are willing and able to learn on their own initiative , with or without the help of other parties in terms of determining learning objectives, learning methods, and evaluating learning outcomes. According to (Mujiman 2005 in (Aliyyah & Djuanda, 2020) the research was conducted using a descriptive quantitative approach. The subjects of this study were students majoring in Computer and Network Engineering, SMK Negeri 1 Ketapang class XII as many as 36 respondents. The results of the discussion show that the learning independence of students is lacking in indicators of not depending on others, discipline, responsibility, initiative and self-control it is proven that only indicators of self-confidence are in a good category Utilization of the application is felt to be less supportive because there are several billing assignments that are not known to have been collected or have not been collected or there is no system in place restrain students from being able to continue to the next material if there are assignments that have not been done. This is one of the declines in the percentage of independent learning. Until a positive value is obtained for future application development in order to increase the percentage of independent learning.